When the Community is Invisible: Corporate Social Responsibility in the Mining Industry - Mansilla Obando, Katherine (2022)
Corporate social responsibility (CSR) initiatives are common in the mining industry and have the watchful eye of their stakeholders. However, limited attention has been given to the perceptions of the host communities regarding these initiatives. This paper seeks to explore the perceptions of a host community, located in the north of Chile, regarding the CSR initiatives of mining companies close to their community. Through a qualitative methodology, nine semi-structured interviews (to residents and workers of the host community) are conducted. The data are analyzed with the thematic analysis technique and, together with the theoretical lenses of the CSR pyramid and the stakeholder theory, the results are obtained. The main findings indicate that the host community perceives different responsibilities regarding the CSR initiatives of the mining industry. These dimensions comprise the level of importance perceived by the community, from the bottom (most important) to the top of the pyramid (least important), such as environmental responsibility, responsibility for health and safety well-being, ethical responsibility, economic responsibility, legal responsibility, and finally, philanthropic responsibility. The investigation contributes to the literature on CSR in the mining industry, generating practical implications for public policies, the management of mining companies and the leaders of the host community.